Finite difference time domain method of light propagation through inhomogeneous media - Milosevic, M.; Stevanovic, N.; Markovic, V. M.; Cimbaljevic, Z. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Propagation of arbitrarily polarized light through inhomogeneous media is modeled in this paper. The model can include parameters of the media such as relative dielectric constant, relative magnetic constant and electric conductivity. The orientation of the electric field strength of the light source could be defined arbitrarily, and in this paper two polarization modes are considered: transverse electric (TE) mode and transverse magnetic (TM) mode. The electric field vector could change its orientation in dependence on the characteristics of the media. The model developed in this paper is based on the finite difference time domain (FDTD) method and Maxwell’s equations. A two-dimensional formulation of FDTD is applied in this computing. Several cases were considered, and the results obtained in this paper agree with the literature. The model shown in this paper does not require much time for computer processing and can be easily applied for specific cases of media, source, and light.
Optica Applicata, Vol. 53, 2023, nr 4, s. 523-538
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; FDTD method; light propagation; optics